The intricate relationship of vitamin-D with Arterial Stiffness: A case control study on middle-aged Indian population with an insight from the mechanistic pathways providing special reference to endothelial dysfunction and oxygen sensing proteins - Podder, Amrit; M Patil, Sumangala; Khodnapur, Jyoti P; Das, Kusal K; Badiger, Sharan; Kumar, Jayballabh; Adhana, Ritu (Journal of Neonatal Surgery, 2025)
Introduction: Arterial stiffness (AS) is recognized as a crucial predictor of cardiovascular events, particularly in middle-aged individuals. Meanwhile, the role of vitamin D in cardiovascular health has garnered significant attention. Emerging evidence suggests a potential link between the level of serum total vitamin D status and AS, although the underlying mechanisms remain incompletely understood. Our case control study aims to elucidate the intricate relationship of serum total vitamin D with AS and explore the potential mechanistic pathways in the middle-aged population. Materials and Methods: 108 age-matched participants of both genders were divided into three groups according to their hypertension (HTN) status following the latest American Heart Association (AHA) guidelines. Individuals having normal blood pressure (BP) were considered participants of Group 1 (control group) whereas the stage-I hypertensive individuals were considered participants of Group 2 and stage-II hypertensive participants were considered participants of Group 3. All the participants were assessed for their level of serum total vitamin D, arterial stiffness index (ASI) and pulse wave velocity (PWV). The data was entered into a Microsoft Excel Sheet and analyzed using SPSS software (version 25). Results: ASIs of different limbs and PWVs were found to be increased in age-matched both the hypertensive groups participants as compared to the normotensive (control) group. Serum total vitamin D level was also found to be lower in both the hypertensive groups when compared with the normotensive (control) group. We found a negative correlation between parameters of the arterial stiffness and level of serum total vitamin D. We also found a negative correlation between the components of BP and serum total vitamin D. Conclusion: We conclude our study by finding a beneficial role of vitamin D for reducing AS which in turn influences to decrease the BP and results in lower events of cardiovascular morbidities.